Konstruksi Sosial-Teologis Ritual Ijazah Asma' Artho (Uang Azimat) di Pondok Pesantren Fathul Ulum Kwagean Pare Kediri - Mukhammad Zamzami (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2018)
This article scrutinizes social and theological constructions of the practice of ijazah Asma Artho or Uang Azimat (money blessing tradition) in Fathul Ulum Islamic Boarding School. Asma Artho is not a practice of doubling money. It is only money blessed by Kiai. There is a symbol contained in the post-blessing money, the kiai, through his team, writes the word Bāsiț, one of Asmā’ al-Ḥusnā, on the blessed money. Socially, the practice, which is routinely implemented every year, is not only sought by the santri, but also the general public and businessmen. If santri and the general public wishes the blessing of their rejection from this ritual process, then it is different from the perspective of the business community, where they believe this money (Asma Artho) has enough impact on the increase in the business's current good. For them, the more blessed the money is, the more fortune it earns. In understanding the theological construct of this blessed money, the author examines the meaning of the Bâsiṭ, one of Asmā' al-Ḥusnā, and the interpretation of this word in the Qur'ân which is contained in the money, and how to read the rajah. This blessed money is based on the thought of Abū Ḥāmid al-Ghazālī, Abū Bakr Muḥammad Shatā al-Dimyātī, and Ma‘rūf al-Karkhī. Al-Karkhī said has even said that anyone who reads the mawlid upon the Prophet Muhammad on some silver or gold-plated dirhams and then mix the dirhams with other dirhams, these dirhams will then get a blessing.